The Intersection Of Law and Culture: How Traditional Practices Shape Legal Norms in Multicultural Societies - Batbayar Enkhtaivan; Tserendorj Myagmarsuren; Uugantsetseg Munkhbat (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
This study explores the influence of cultural traditions on the formation and adaptation of legal norms in multicultural societies. By analyzing cases from countries with diverse ethnic groups, the article evaluates how traditional practices sometimes conflict with formal legal standards, particularly in family and property law. Findings indicate the importance of incorporating cultural considerations into legal frameworks to enhance social cohesion while ensuring justice and equality.